Perancangan Interior Butik dan Kafe “TOPSHOP” di Surabaya - Jessica Cynthia Haryono; Hedy Constancia Indrani; Fenny Kurnia Dewi (Intra, 2013)
Development of fashion and culinary in Indonesia is growing rapidly. Boutiques and cafes are very identical to human life. For this design of Topshop boutique and café in Surabaya have some facilities such as boutiques, cafes, fashion show area, nail art station, clothing reparation area and children’s play area. The concept is “Oxford Street” which is the name of the first place that Topshop was established, in London. The atmosphere that want to be created in this design is the atmosphere of city street which is surrounded by shop, café and another public facilities are also widely encountered along the way.